The human Vδ2+ T-cell compartment comprises distinct innate-like Vγ9+ and adaptive Vγ9- subsets - Davey, Martin S; Willcox, Carrie R; Hunter, Stuart; Kasatskaya, Sofya A; Remmerswaal, Ester B M; Salim, Mahboob; Mohammed, Fiyaz; Bemelman, Frederike J; Chudakov, Dmitriy M; Oo, Ye H; Willcox, Benjamin E (Nature communications, 2018)
Vδ2+ T cells form the predominant human γδ T-cell population in peripheral blood and mediate T-cell receptor (TCR)-dependent anti-microbial and anti-tumour immunity. Here we show that the Vδ2+ compartment comprises both innate-like and adaptive subsets. Vγ9+ Vδ2+ T cells display semi-invariant TCR repertoires, featuring public Vγ9 TCR sequences equivalent in cord and adult blood. By contrast, we also identify a separate, Vγ9- Vδ2+ T-cell subset that typically has a CD27hiCCR7+CD28+IL-7Rα+ naive-like phenotype and a diverse TCR repertoire, however in response to viral infection, undergoes clonal expansion and differentiation to a CD27loCD45RA+CX3CR1+granzymeA/B+ effector phenotype. Consistent with a function in solid tissue immunosurveillance, we detect human intrahepatic Vγ9- Vδ2+ T cells featuring dominant clonal expansions and an effector phenotype. These findings redefine human γδ T-cell subsets by delineating the Vδ2+ T-cell compartment into innate-like (Vγ9+) and adaptive (Vγ9-) subsets, which have distinct functions in microbial immunosurveillance.
Keywords: kultivované buňky; buněčné klony; Immunophenotyping; průtoková cytometrie; imunofenotypizace; Cell Differentiation; Receptors, Antigen, T-Cell, gamma-delta; Cytomegalovirus; receptory antigenů T-buněk gama-delta; Cell Proliferation; Adult; Flow Cytometry; Cells, Cultured; Infant, Newborn; novorozenec; Humans; proliferace buněk; buněčná diferenciace; T-Lymphocyte Subsets; dospělí; Clone Cells; T-lymfocyty - podskupiny; lidé